Salmonella species causing hip septic arthritis - Alhazzazi, Khalid Mohammed A.; Alsheikh, Khalid; Konbaz, Faisal; AlMugren, Turki Saud (International Journal Of Community Medicine And Public Health, 2018)
Salmonella infection has been associated with various presentations depending on the system that has been affected and Salmonella species that invaded the body. Usually present with gastroenteritis symptoms and bacteremia. Rare cases had been recorded that Salmonella causing septic arthritis. We are reporting a rare case of Salmonella causing septic hip arthritis. Case report of a 31-year-old lady, known case of: systemic lupus erythematosus, anti-phospholipid syndrome, chronic kidney disease from National Guard Hospital, Riyadh, Saudi Arabia, 2018. We found the possibility of Salmonella species that causes various diseases can cause septic hip arthritis. Salmonella gram-negative bacilli has been associated with broad spectrum of illnesses as gastroenteritis, typhoid fever and septicemia. In the developed countries Salmonella cause self-limiting diarrhea with risk of developing bacteremia. Rare cases reported as a case of Salmonella causing septic joint arthritis. Following the recommendations of treating Salmonella osteomyelitis would help eradicate the infection and decrease the relapse rate period.